Stigmasta-7-,16,25(26)-Triene-3-O-β-D-Glucopyranosyl-(1→5)-O-β-D-Xylofuranoside from the Roots of Vitis adnata - Srivastava, Mahesh (Asian Journal of Chemistry, 2010)
The present communication deals with the isolation and identification of the saponin stigmasta-7, 16,25(26)-triene-3-O- β -Dglucopyranosyl- (1→5)-O-β -D-Xylofuranoside from the roots of Vitis adnata.